SISTEM INFORMASI PENJADWALAN MATA PELAJARAN BERBASIS WEB - Udin Sidik Sidin (semanTIK, 2016)
This research is the software development that aims to design the Web Based Subjects Scheduling Information System. This system is designed to make management of subjects schedule easier. The development of this software uses waterfall development model with system planning or analysis, system designing, coding, system testing and web maintenance. In building the system, PHP programming language and MySQL are used to store the data. The method used in this research is to look for reference relating to web based scheduling, observation and interview are used to determine the users’ response about the designed information system. The result obtained from the design of this system is a subjects scheduling information system that makes the scheduling process easier so that the learning process can be more effective and efficient. The data collecting by the author to determine the users’ response about the information system that has been designed is by conducting interviews, so it can be concluded that the responses toward the web based subject scheduling information system quality can go well.     Keywords— Information System, Scheduling, Waterfall, PHP and MySQL